Stimuli‐responsive polymer nanocomposites based on styrene‐butadiene rubber and bacterial cellulose whiskers. (2nd February 2018) - Chen, Yang; Li, Geng; Yin, Qing; Jia, Hongbing; Ji, Qingmin; Wang, Liping; Wang, Dongni; Yin, Biao
Abstract : Water‐induced mechanically adaptive rubber nanocomposites were prepared by mixing bacterial cellulose whiskers (BCWs) suspension with styrene‐butadiene rubber (SBR) latex, followed by evaporation method. The structure, morphology, dynamic mechanical properties, water stimuli‐responsive behavior, and biodegradability of SBR/BCWs nanocomposite films were investigated. The results showed that the hydrophilic whiskers had a significant reinforcement effect on the storage modulus of SBR matrix, which originated from the formation of a rigid three‐dimensional filler network within matrix by strong hydrogen bonding between whiskers. The SBR/BCWs nanocomposites showed pronounced water stimuli‐responsive behavior compared with neat SBR. The storage modulus of SBR/BCWs nanocomposite could be decreased by 99.2% after equilibrium water swelling. This remarkable water‐triggered modulus change is attributed to the disentanglement of BCWs network via competitive hydrogen bonding with water.